2012
DOI: 10.1021/ja304176q
|View full text |Cite
|
Sign up to set email alerts
|

A Nucleotide-Analogue-Induced Gain of Function Corrects the Error-Prone Nature of Human DNA Polymerase iota

Abstract: Y-family DNA polymerases participate in replication stress and DNA damage tolerance mechanisms. The properties that allow these enzymes to copy past bulky adducts or distorted template DNA can result in a greater propensity for them to make mistakes. Of the four human Y-family members, human DNA polymerase iota (hpol ι) is the most error-prone. In the current study, we elucidate the molecular basis for improving the fidelity of hpol ι through use of the fixed-conformation nucleotide North-methanocarba-2′-deoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For our docking submissions, we focused on the Y-family DNA polymerases. Multiple crystal structures have been reported for hpol η 1–437 , hpol κ 19–526 , and hpol ι 26–446 . ,,, Both apo and binary coordinate files were submitted to SwissDock for each enzyme. For this discussion, we consider only the apo form since the only observed difference was in the binding pocket near the primer–template DNA/active site interface (pocket A).…”
Section: Discussionmentioning
confidence: 99%
“…For our docking submissions, we focused on the Y-family DNA polymerases. Multiple crystal structures have been reported for hpol η 1–437 , hpol κ 19–526 , and hpol ι 26–446 . ,,, Both apo and binary coordinate files were submitted to SwissDock for each enzyme. For this discussion, we consider only the apo form since the only observed difference was in the binding pocket near the primer–template DNA/active site interface (pocket A).…”
Section: Discussionmentioning
confidence: 99%
“…An siRNA duplex containing a ribo-N-MC modification in the guide strand was taken up by the intracellular RNAi machinery and showed near-wildtype activity and target mRNA degradation (Terrazas et al 2011). A crystal structure of a N-MC-dATP nucleotide bound at the active site of the model DNA polymerase Dpo4 superimposed nearly perfectly with an unmodified dATP bound at the same site, demonstrating selectivity of the polymerase for the North substrate conformation (Ketkar et al 2012a), and no protein contacts to the cyclopropane ring were observed in either Dpo4 or human DNA polymerase iota (Ketkar et al 2012b). Both N-MC and S-MC nucleotides have been shown to reproduce the preferences of the corresponding unmodified nucleotides for rotamers at the sugar-base glycosidic bond (torsion angle χ) and ring-adjacent C3 ′ -C4 ′ bond (γ) (Marquez et al 1997(Marquez et al , 2004.…”
mentioning
confidence: 99%
“…Recently we showed that another Y-family member, human DNA polymerase iota (hpol ι) utilizes N-MC-dATP more efficiently than the unmodified nucleotide. 38 Again, there were no protein contacts near the cyclopropane ring with either N-MC-dATP or S-MC-dATP bound to the hopl ι active site. The primary effect of the bicyclo[3.1.0]hexane moiety was to alter the syn/anti equilibrium such that the adenine group of N-MC-dATP preferentially adopted the anti conformation.…”
Section: ■ Discussionmentioning
confidence: 96%
“…The perturbations associated with S-MC-dADP binding to Dpo4 result from interactions with the 3′-OH group of the nucleotide and the steric gate residue, which wedges the incoming S-MC-dADP into the primer terminus and positions the phosphates poorly for catalysis. Recently we showed that another Y-family member, human DNA polymerase iota (hpol ι) utilizes N-MC-dATP more efficiently than the unmodified nucleotide (38). Again, there were no protein contacts near the cyclopropane ring with either N-MC-dATP or S-MC-dATP bound to the hopl ι active site.…”
Section: Discussionmentioning
confidence: 99%